Contributions of the History and Philosophy of Science and Methodology of Problematization to the Public Health Policies teaching and their connection with the Environment - Rosa, Marllon Moreti de Souza; Gonçalves, Laíse Vieira; Nascimento Júnior, Antônio Fernandes (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This paper aims to report and analyze a pedagogical practice developed for Public Health Policies teaching in a course held at the Federal University of Lavras, in the first semester of 2018. For the development of this paper, a class was created and taught in a Public Health Policies teaching course based on the History and Philosophy of Science and Problem-solving Methodology, seeking to understand how these pedagogical strategies contribute to the teaching of this theme and its connection with the environment. At the end of the class, students were asked to evaluate the practice, pointing out the strengths and points to be improved. These feedbacks were organized and analyzed qualitatively through the Content Analysis and, later, were discussed. The results of the analyzes indicate that Environmental Education cannot be conservative of social conditions, but rather present the connection between man and nature, highlighting the link between the exploration of nature and the production of goods. In addition, the History and Philosophy of Science, starting with questions about the reality of students, can enhance the teaching-learning process, since it can avoid fragmentation of knowledge, allowing an approximation of students to scientific knowledge and its social use.